2015
DOI: 10.1002/pon.3964
|View full text |Cite
|
Sign up to set email alerts
|

Emotional responses to the experience of cancer ‘alarm’ symptoms

Abstract: ObjectiveTo qualitatively explore associations between emotional responses to experience of cancer ‘alarm’ symptoms and help‐seeking in a community sample of adults.MethodInterviewees (n = 62) were recruited from a community sample (n = 2042) of adults aged ≥50 years, who had completed a health survey that included a list of cancer alarm symptoms. Participants who had reported an alarm symptom both at baseline and 3‐month follow‐up (n = 271), and who had consented to contact (n = 215), constituted the pool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
4
21
0
1
Order By: Relevance
“…Death associations were more common among those with lower levels of education, from regions with higher cancer mortality, and among those with previous experience of cancer in others. This is consistent with suggestions by other authors that fatalistic cancer attitudes may be the indirect consequence of under‐education and poverty, leading to a focus on day‐to‐day survival rather than health‐promoting behaviours, and potentially causing delays in help‐seeking for symptoms and poorer cancer outcomes . Fatalistic beliefs in families and communities may be reinforced by witnessing this cycle of poorer cancer outcomes .…”
Section: Discussionsupporting
confidence: 87%
“…Death associations were more common among those with lower levels of education, from regions with higher cancer mortality, and among those with previous experience of cancer in others. This is consistent with suggestions by other authors that fatalistic cancer attitudes may be the indirect consequence of under‐education and poverty, leading to a focus on day‐to‐day survival rather than health‐promoting behaviours, and potentially causing delays in help‐seeking for symptoms and poorer cancer outcomes . Fatalistic beliefs in families and communities may be reinforced by witnessing this cycle of poorer cancer outcomes .…”
Section: Discussionsupporting
confidence: 87%
“…Despite these limitations, we feel confident that we have presented a robust taxonomy of cancer fears in the context of cancer screening, because of the large number of triangulated studies, the diversity of the study samples, and the fact that the updated literature search only identified a single new subtheme. In addition, many of the fears described in this review have also been described in studies of other types of cancer screening, help‐seeking for cancer symptoms genetic cancer risk, and cancer patients, lending further support to the idea that the cancer fears identified in this review are universal.…”
Section: Discussionsupporting
confidence: 65%
“…One potential explanation is the mixed role of emotion in help-seeking [31], where cancer worry can act both as a barrier and facilitator to contacting a health care professional [32]. …”
Section: Discussionmentioning
confidence: 99%